Motivasi dan Upaya Peningkatan Perekonomian melalui Wirausaha - Ari Ani Dyah Setyoningrum; Deri Herdawan (Universitas Islam Kadiri, 2022)
This study aims to provide an overview of the entrepreneurial motivations that encourage married women to become entrepreneurs and explore the efforts of women in entrepreneurship in improving their family economy. Entrepreneurship is a way that can help the family economy and become a self-actualization tool for women. This research was conducted with a qualitative approach. The sample of this research was selected by random sampling technique. The data were collected by using interviews, questionnaires and observation. The results of this study revealed that the motivation of women in entrepreneurship, among others, because of the desire to be economically independent, fulfilling the family's daily needs, spending spare time, utilizing existing places for business, hobbies, being motivated by other people, and having certain skills. Efforts to improve the family economy by entrepreneurship have a positive impact on improving the family's economic condition. With good financial management, the family's economic condition will improve. Entrepreneurial women share their income for several needs, including for the needs of their business continuity, family needs and investing. Keywords: Entrepreneur, motivation, economy.